2011
DOI: 10.1128/aem.01918-10
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a Human Norovirus Surrogate by High-Pressure Processing: Effectiveness, Mechanism, and Potential Application in the Fresh Produce Industry

Abstract: Fresh produce is often a high-risk food for norovirus contamination because it can become contaminated at both preharvest and postharvest stages and it undergoes minimal or no processing. Currently, there is no effective method to eliminate the viruses from fresh produce. This study systematically investigated the effectiveness of high-pressure processing (HPP) on inactivating murine norovirus (MNV-1), a surrogate for human norovirus, in aqueous medium and fresh produce. We demonstrated that MNV-1 was effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 59 publications
(160 reference statements)
12
129
3
Order By: Relevance
“…Tang et al (30) demonstrated that the RNA of MNV-1 was protected from RNase treatment after a 400-MPa treatment, which suggests that the viral capsid remained intact. However, a recent electron microscopy-based study by Lou et al (31) showed that a 600-MPa treatment was able to destroy MNV-1 capsid integrity and prevent release of viral genomic RNA. In the present study, HHP treatments of 400 to 600 MPa at 25°C caused 2-foldhigher log 10 reductions of RT-PCR-detectable RNA in the GII.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al (30) demonstrated that the RNA of MNV-1 was protected from RNase treatment after a 400-MPa treatment, which suggests that the viral capsid remained intact. However, a recent electron microscopy-based study by Lou et al (31) showed that a 600-MPa treatment was able to destroy MNV-1 capsid integrity and prevent release of viral genomic RNA. In the present study, HHP treatments of 400 to 600 MPa at 25°C caused 2-foldhigher log 10 reductions of RT-PCR-detectable RNA in the GII.…”
Section: Discussionmentioning
confidence: 99%
“…As a separate issue, it is likely that different HuNoV genogroups will exhibit differing levels of environmental persistence (e.g., water [8] and surfaces [21]), infectivity (18)(19)(20), and resistance to inactivation (7,13,15,28). Several groups have proposed that differences in environmental persistence, infectivity, and resistance to inactivation between the genogroups and strains may be due to differences in the stability of the HuNoV capsid coat (8), which influence the viral receptor binding and entry mechanisms of HuNoV (24,33) (including the contribution of the histoblood group antigens (reviewed in references 31 and 32). These hypotheses may also explain our unpublished analyses of a systematic review of 900 HuNoV outbreaks (between 1983 and 2010) in which we found that genogroup I strains, rather than genogroup II strains, were significantly more likely to be associated with waterborne outbreaks (data not shown) and that GII-associated outbreaks had a significantly lower prevalence of foodborne outbreaks (data not shown) (J. Matthews, B. Dickey, R. Miller, J. Felzer, B. Dawson, A. Lee, J.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the use of HHP on contaminated oysters and clams found that 300 MPa did not inactivate GI and GII noroviruses (63). Several studies on the use of HHP to inactivate surrogate viruses seeded in a variety of nonfood matrices have been published (47,62,(64)(65)(66)(67)(68). Unfortunately, a wide variety of experimental conditions and a limited range of pressures for the evaluation of each virus were used, making these results very difficult to compare across the different surrogate viruses.…”
Section: Fig 7 Reductions In Tuv Infectivity and In Tuv And Human Normentioning
confidence: 99%